Internalized stigma among patients with substance use disorders at a tertiary care center in India. Issue 3 (3rd July 2019) - Sarkar, Siddharth; Balhara, Yatan Pal Singh; Kumar, Saurabh; Saini, Vinay; Kamran, Akriti; Patil, Vaibhav; Singh, Swarndeep; Gyawali, Shreeya
ABSTRACT: Internalized stigma among individuals with substance use disorders is a major barrier for accessing mental health services. This study aimed to assess internalized stigma among individuals with substance use disorders and to assess the relationship of internalized stigma with the quality of life. This cross-sectional study recruited 201 patients with a clinical diagnosis of at least opioid or alcohol use disorder according to Diagnostic and Statistical Manual 5 at a public-funded tertiary care center in India. The study participants were interviewed using a sociodemographic questionnaire, the Internalized Stigma of Mental Illness Scale (ISMIS), and the World Health Organization's Quality of Life (WHOQOL-Bref) questionnaire. Seven participants (3.5% of the sample) had mild stigma according to ISMI scores, 62 (30.8%) had moderate stigma, and 132 (65.7%) had severe stigma. The various quality-of-life domains generally had a negative correlation with the internalized stigma scores. Participants using opioids as the primary substance of use were more likely to have severe internalized stigma. The experience of internalized stigma and dissatisfaction with quality of life is quite high among people suffering with substance use disorders in India. These results emphasize the need for interventions to reduce internal perception of stigma and improve the quality of life of individuals with substance use disorders.